2019
DOI: 10.4102/sajems.v22i1.2412
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of employer branding on staff retention and compensation expectations

Abstract: Background: In a highly competitive, economically strained business environment it is essential for a business to balance the necessity of attracting and retaining top-performing employees and containing costs. Employee branding is a management tool that can serve to retain staff and reduce compensation levels.Aim: This study investigated the effects of employee branding on staff retention and compensation expectations.Setting: Five South African insurers participated in this research.Methods: Analysis of vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 21 publications
4
30
1
1
Order By: Relevance
“…The results of t-test assert that no significant difference exists between male and female employees for both employee attraction and retention factors. The findings are in line with the previous studies, where authors reported non-significant differences for EB factors in terms of gender (Ahmad et al, 2019;Bussin and Mouton, 2019;Chandler, 2019). The insignificant results could adhere to the volatile job market (Sengupta et al, 2015), due to which male and female employees have similar value preferences while searching for new jobs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The results of t-test assert that no significant difference exists between male and female employees for both employee attraction and retention factors. The findings are in line with the previous studies, where authors reported non-significant differences for EB factors in terms of gender (Ahmad et al, 2019;Bussin and Mouton, 2019;Chandler, 2019). The insignificant results could adhere to the volatile job market (Sengupta et al, 2015), due to which male and female employees have similar value preferences while searching for new jobs.…”
Section: Discussionsupporting
confidence: 93%
“…Past findings implicate that employees have similar attribute preferences that attract and retain them irrespective of gender (Sengupta et al, 2015;Chandler, 2019). Bussin and Mouton (2019) connoted that the demographic variable of gender did not affect the perception people had of branding attributes and their relative attractiveness. Similarly, Ahmad et al (2019) reported insignificant differences in gender concerning employee attraction and retention factors.…”
Section: Employer Branding and Demographic Variablesmentioning
confidence: 97%
“…Prior studies explicate that employees are interested in working for an organization that is socially responsible and avoids activities that harm society (Biswas & Suar, 2014). Researchers provide that signalling CSR values have the ability to influence job satisfaction (Tanwar & Prasad, 2016b), intent to join (Sharma & Prasad, 2018), where few studies have also examined its effect on retention of employees (Bussin & Mouton, 2019; Tanwar & Prasad, 2016a). Given the depth of research on the impact of CSR on various stakeholders, there exists a lack of empirical research on its likely influence on ER from the perspective of another set of stakeholders, that is, current employees (Raub & Blunschi, 2014; Tanwar & Prasad, 2017).…”
Section: Developing Hypothesesmentioning
confidence: 99%
“…With a growing body of research on EB as a talent attraction and retention tool, the majority of companies have entailed corporate social responsibility (CSR) activities in their EB strategies. Where past researchers have tested the relationship between EB and employee retention (ER) (Kashyap and Verma, 2018;Bussin and Mouton, 2019), empirical studies that consider the role of CSR are limited. CSR as an EB dimension emphasizes on its value as a competitive tool (Tanwar and Prasad, 2017;Sharma and Prasad, 2018;Carlini et al, 2019;Tanwar and Kumar, 2019) where the efforts of organizations to embed ethical stance in their policies, practices and procedures have been noted to influence employees' behavior (Carlini et al, 2019).…”
Section: Introductionmentioning
confidence: 99%